Study on Applications and Business Models of eMBMS - Dandan Qin; Jiangang Tong; Zheng Wang; Jiayu Bi (Dianxin kexue)
eMBMS business concept was first introduced to analyze the specific business application scenarios of live services and push services, followed by analysis of the whole industrial ecosystem, charging model, content aggregation methods, business management requirements, and business promotion strategy. It was proposed that the platform model was the best business model in the primary stage. In addition, combined with the advantages of the content model, developing telecom operators' unified client was proposed in order to strengthen telecom operators' brand marketing.